Long-term functional, subjective and psychological results after single digit replantation - Jing Chen; Ai Xian Zhang; Qing Zhong Chen; Shuai Mu; Jun Tan (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to analyse the long-term functional, subjective, and psychological results after single-digit replantation. Methods: Thirty cases of digital replantation (14 thumbs, 12 index fingers, 2 middle fingers, 1 ring finger, and 1 little finger) in 30 patients (7 females and 23 males) with a mean age of 44.2 years (20–65 years) were evaluated at the end of a mean follow-up time of 36 months (19–50 months). The active range of motion of joints, grip and pinch strength, cutaneous sensibility, upper-extremity functioning, and subjective satisfaction were determined using the Disability of Arm, Shoulder, and Hand (DASH) questionnaire and the Michigan Hand Outcomes questionnaire (MHQ). Psychological sequelae, including depression, anxiety, and posttraumatic stress disorder (PTSD), were assessed. A correlation analysis among variables was also performed. Results: The mean score for the DASH questionnaire was 6.6 (range: 0–39.2). The symptom of cold intolerance occurred in 53% of the patients. Two patients were diagnosed with depression, and only one patient exhibited PTSD. The DASH score had a good statistical correlation with total grip strength, pinch grip strength, and static two-point discrimination (S-2PD) (P < 0.05). Several aspects of the MHQ were also statistically relevant to some or all of the three objective results. Furthermore, the grip strength showed significant correlation with DASH and most aspects of the MHQ in multivariate logistic regression analysis (P < 0.05). Conclusion: Total grip strength is the most important factor positively related to subjective outcomes. The incidence rates of psychological symptoms after digit replantation are very low at long-term follow-up. Level of evidence: Level IV, therapeutic study. Keywords: Digit Replantation, DASH score, Posttraumatic stress disorder